Temperature Dependence of Single Step Hydrodeoxygenation of Liquid Phase Pyrolysis Oil - Treusch, Klara; Schwaiger, Nikolaus; Schlackl, Klaus; Nagl, Roland; Pucher, Peter; Siebenhofer, Matthäus (Frontiers in Chemistry, 2018)
IIn this paper, continuous hydrodeoxygenation (HDO) of liquid phase pyrolysis (LPP) oil in lab-scale is discussed. Pyrolysis oil is derived from the bioCRACK pilot plant at the OMV refinery in Vienna/ Schwechat. Three hydrodeoxygenation temperature set points at 350°C, 375°C and 400°C were investigated. Liquid hourly space velocity (LHSV) was 0.5 h-1. Hydrodeoxygenation was performed with an in situ sulfided metal oxide catalyst. During HDO, three product phases were collected. A gaseous phase, an aqueous phase and a hydrocarbon phase. Experiment duration was 36 hours at 350°C and 375°C and 27.5 hours at 400°C in steady state operation mode. Water content of the hydrocarbon phase was reduced to below 0.05 wt.%. The water content of the aqueous phase was between 96.9 wt.% and 99.9 wt.%, indicating effective hydrodeoxygenation. The most promising results, concerning the rate of hydrodeoxygenation, were achieved at 400°C. After 36 / 27.5 hours of experiment, catalyst deactivation was observed.